The Influence of the Structural Features of Molecules on Spontaneous Polarization Value in Induced Ferroelectric Liquid Crystal Systems - Bezhanova, L. S.; Atanesyan, A. K.
The occurrence of the large value of spontaneous polarization is established in LC system whose composition`s molecular structure does not satisfy the obligatory conditions for the occurrence of spontaneous polarization that are imposed by theory on a molecular structure. The essential role of short range intermolecular forces in the process of ferroelectric phase transition in the studied LC systems is shown. It was found that for CC, DD and AD interactions the most beneficial molecules` packing in terms of energy is the antiparallel one . In the case of AA and AC interactions both parallel and are equally beneficial in terms of energy. The possibility of formation of molecular clusters–dimers is shown. It is concluded that these are stabilized, in particular, by dipole–dipole interaction of molecules. A dimer model for increasing the value of spontaneous polarization is proposed.
Keywords: Physics